A Systematic Review of Flipped Classroom for English Learning Teaching(ELT) - Zulfa Zulfa; Marwa Alifa Khanza; Naf’an Tarihoran (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The Flipped Classroom is an innovative approach in teaching English as a Foreign Language (EFL) that delivers materials before class and uses in-class time for interactive learning. Rooted in constructivist and multimedia learning theories, this method encourages active, student-centered engagement supported by technology. Using the PRISMA framework, this review analyzes 30 selected studies from 50 initial publications to explore its effectiveness, benefits, challenges, and success factors in English Language Teaching (ELT). Results show that the approach enhances speaking and writing skills, learner autonomy, and motivation, while reducing language anxiety. However, issues like limited technology access, students’ lack of readiness, and increased teacher workload persist. The study concludes that effective implementation requires strong technological support, student preparedness, and active teacher involvement. Despite challenges, the Flipped Classroom offers great potential for improving EFL learning outcomes.